As We Were Saying : Sewanee Writers on Writing - Latham, Adam; Roberts, Megan, 1980-; Prunty, Wyatt (Book collections on Project MUSE., 2021)
"Every summer for the past thirty years, the Sewanee Writers' Conference has gathered a community of writers for two weeks of workshops, readings, talks, and meetings focused on the craft and art of writing. This book is a selection of craft talks delivered during the conference over the last several years. Some essays focus on one or two authors, some focus on texts, while others cast their regard more broadly. All are written in response to questions generated by the process of writing, as masters of the craft candidly report challenges they confront and the means by which they work to resolve such issues. The eighteen essays encompass poetry, fiction, and playwriting, investigating questions of language, character, design, and meaning, with nuanced readings of particular authors and works alongside more wide-ranging reflections on craft. Designed for audiences of writers and readers across multiple levels and backgrounds, the essays collected in "As We Were Saying" offer original, insightful arguments about the craft of writing and the power of literature"--